IL33 and Mast Cells—The Key Regulators of Immune Responses in Gastrointestinal Cancers? - Eissmann, Moritz F.; Buchert, Michael; Ernst, Matthias (Frontiers in Immunology, 2020)
The Interleukin (IL-)1 family IL33 is best known for eliciting type 2 immune responses by stimulating mast cells (MCs), regulatory T-cells (Tregs), innate lymphoid cells (ILCs) and other immune cells. MCs and IL33 provide critical control of immunological and epithelial homeostasis in the gastro-intestinal (GI) tract. Meanwhile, the role of MCs in solid malignancies appears tissue-specific with both pro and anti-tumorigenic activities. Likewise, IL33 signaling significantly shapes immune responses in the tumor microenvironment, but these effects remain often dichotomous when assessed in experimental models of cancer. Thus, the balance between tumor suppressing and tumor promoting activities of IL33 are highly context dependent, and most likely dictated by the mixture of cell types responding to IL33. Adding to this complexity is the promiscuous nature by which MCs respond to cytokines other than IL33 and release chemotactic factors that recruit immune cells into the tumor microenvironment. In this review, we integrate the outcomes of recent studies on the role of MCs and IL33 in cancer with our own observations in the GI tract. We propose a working model where the most abundant IL33 responsive immune cell type is likely to dictate an overall tumor-supporting or tumor suppressing outcome in vivo. We discuss how these opposing responses affect the therapeutic potential of targeting MC and IL33, and highlight the caveats and challenges facing our ability to effectively harness MCs and IL33 biology for anti-cancer immunotherapy.